Effect of Cutting Parameters on Tool Wear when Trochoidal Pocket Milling Ti6Al4V - Sharif, S.; Ramli, A. S.; Said, A. Y. M.; Karim, Z.; Rahim, E. A.; Abdul Sani, A. S. (International Journal of Integrated Engineering, 2019)
Despite being an attractive material for aerospace components such as engine parts and airframes, titanium alloy is categorized as a difficult-to-machine material which results in rapid tool wear and tool failure. It was reported that trochoidal machining method is preferred as compared to conventional machining due to its ability to prolong the tool life. This machining technique has the ability to reduce the load and provide enough space for the chips to evacuate and allowing sufficient time for the tool to be cooled. This study was conducted to investigate the effect of cutting parameters on the tool wear of TiAlN/TiN coated carbide tool when trochoidal milling Ti6Al4V under wet condition. Design of experiment based on response surface method (RSM) was adopted with three factors (cutting speed, feed rate and step over), two levels and five centre points with a total of 17 experimental runs. The cutting speed (Vc) was set at 60 to 90 m/min, feed rate (fz) at 0.06 to 0.1 mm/tooth and step over (ae) at 1.5 to 2.5 mm. The experimental results indicated that cutting speed was the dominant factor affecting the tool wear, followed by feed rate and lastly the step over. ANOVA results showed that all three cutting parameters exhibit positive interaction towards wear condition thus implying that higher value of cutting speed, feed rate and step over resulted in rapid tool wear and shorten the tool life.